PENGARUH KONFORMITAS DAN SELF-EFFICACY TERHADAP KOMPETENSI PEDAGOGIK GURU MGMP EKONOMI SE-KOTA SINTANG - Rizal, Syamsu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The aim of this study to describe : 1) the influence of Conformity to the Pedagogical Competence of teachers, 2)self-efficacy of the pedagogical competence of teachers; 3)conformity and self-efficacy of the pedagogical competence of teachers. The approach used in this study was a quantitative survey method. Data collection techniques used are questionnaires and interviews and data collection tool questionnaire and interview guides. Data processing techniques used multiple linear regression techniques. The results of this study indicate that conformity had a significant influence on Competence Pedagogical teacher MGMPs Economy, Self-Efficacy has a significant influence on Competence Pedagogical teacher MGMPs Economics, Variable Conformity and Self-Efficacy jointly significant effect on the dependent Competence Pedagogical teacher MGMPs Economy. The calculations show the coefficient of determination shown Adjusted R-Square value of 0.342. The conclusion that 34.20% of dependent ie pedagogic influenced by two independent ie conformity and self-efficacy, while the remaining 65.80% of pedagogic competence is influenced by other variables Keywords: Conformity, Self-Efficacy and Pedagogic Competence